The Conferral of the National Hero Title on Soeharto: A Comparative Framing Analysis of ANTARA and Tempo - Hayiz Historia Adhi Pratama; Achmad Kanzulfikar; Lisy Tantowi (Universitas Ahmad Dahlan, 2026)
The conferral of the National Hero title upon Soeharto has sparked widespread criticism and controversy where the media play a vital role in shaping public perceptions of the government’s decision. This study aims to analyze how news media frame the discourse surrounding the conferral of the National Hero title on Soeharto. This research employs a qualitative approach using Robert M. Entman’s framing analysis, which comprises four analytical elements: problem definition, causal diagnosis, moral evaluation, and treatment recommendation. The study examines news coverage published by ANTARA and Tempo. The findings reveal contrasting framing patterns between the two media outlets. ANTARA frames the issue as national recognition of Soeharto’s contributions to development and political stability. The controversy is viewed as reflecting different public perspectives. At the same time, the moral evaluation highlights appreciation for historical services, and the treatment recommendation centers on institutional procedures in granting the National Hero title. In contrast, Tempo presents the issue as a controversial political decision amid ongoing debates over human rights violations and corruption. Its coverage underscores the ethical implications of honoring a contested historical figure and argues that the decision is inappropriate given these unresolved controversies. These findings show how different editorial perspectives influence media framing and create competing narratives of historical legitimacy within Indonesia’s political memory.